2008
DOI: 10.1016/j.jhealeco.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Is obesity contagious? Social networks vs. environmental factors in the obesity epidemic

Abstract: This note's aim is to investigate the sensitivity of Christakis and Fowler's claim [Christakis, N., Fowler, J., 2007. The spread of obesity in a large social network over 32 years. The New England Journal of Medicine 357, 370-379] that obesity has spread through social networks. It is well known in the economics literature that failure to include contextual effects can lead to spurious inference on "social network effects." We replicate the NEJM results using their specification and a complementary dataset. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
330
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(343 citation statements)
references
References 14 publications
4
330
0
4
Order By: Relevance
“…In a widely debated article, Christakis and Fowler (2007), using a 32-year panel dataset on adults from Framingham, Massachusetts and based on a logit specification, found that an individual's probability of becoming obese increased by 57% if he or she had a friend who became obese in a given interval. However, their analysis has been criticized for suffering from a number of limitations (see Cohen-Cole and Fletcher, 2008;Lyons, 2011;Shalizi and Thomas, 2011). 8 In particular, it ignores potential spurious correlations between two friends' BMI resulting from the fact that they are exposed to a same environment.…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a widely debated article, Christakis and Fowler (2007), using a 32-year panel dataset on adults from Framingham, Massachusetts and based on a logit specification, found that an individual's probability of becoming obese increased by 57% if he or she had a friend who became obese in a given interval. However, their analysis has been criticized for suffering from a number of limitations (see Cohen-Cole and Fletcher, 2008;Lyons, 2011;Shalizi and Thomas, 2011). 8 In particular, it ignores potential spurious correlations between two friends' BMI resulting from the fact that they are exposed to a same environment.…”
Section: Previous Literaturementioning
confidence: 99%
“…Indeed, most of the relevant literature attempts to estimate the relationship between variables such as an individual's Body Mass Index (BMI) and his average peers' BMI, without exploring the channels at source of this potential linkage. 3 The aim of this paper is to go beyond the black box approach of peer effects in weight gain and try to identify one crucial mechanism through which peer effects in adolescence overweight may flow: eating habits (as 1 While Cohen-Cole and Fletcher (2008) found that there is no evidence of peer effects in weight gain, most of the literature is consistent with the presence of these effects. 2 Researchers also found that friends had a significant effect in adolescent smoking, drinking, illicit drug use (Clark and Loheac, 2007) and risky sex (Jaccard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…31 The built environment encompasses the constructed and open spaces outside the family home, including commercial and noncommercial buildings, public open areas, such as parks playgrounds and green spaces, and road and transportation infrastructure. 32 Features of the built environment such as unfavorable community design and poor transportation infrastructure are associated with decreased energy expenditure.…”
Section: The Role Of the Built Environmentmentioning
confidence: 99%
“…To enhance understanding of food-related decisions, prior research mainly focuses on social influence as an explanatory factor (e.g., Baker, 1986;Christakis & Fowler, 2007;Cohen-Cole & Fletcher, 2008;McFerran, Dahl, Fitzsimons, & Morales, 2010a, 2010b, because it is considered "greater than any other influence on eating" (Herman, Polivy, & Roth, 2003, p. 883). From an analysis of food consumption and body weight across a social network of family and friends over 32 years, Christakis and Fowler (2007) conclude that obesity is contagious, such that people within the network influence one another with regard to their body weight.…”
mentioning
confidence: 99%
“…From an analysis of food consumption and body weight across a social network of family and friends over 32 years, Christakis and Fowler (2007) conclude that obesity is contagious, such that people within the network influence one another with regard to their body weight. Cohen-Cole and Fletcher (2008) instead point to the influence of the shared environment, and other studies focus on the social influence of strangers. For example, McFerran et al (2010a) investigate snacking habits during movies by considering the amount of food that participants consumed in the presence of a stranger.…”
mentioning
confidence: 99%